Family Ownership, Corporate Governance, and Tax Aggressiveness - Ida Subaida; Triska Dewi Pramitasari (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
Companies generally prefer to pay small amounts of tax and use aggressive taxation strategies. This study aims to examine the effect of family ownership on tax aggressiveness moderated by corporate governance. Family ownership is measured by dummy variable 1 or 0, corporate governance with the proportion of the composition of independent commissioners, and tax aggressiveness using the Effective Tax Rate (ETR) on consumer goods companies listed on the Indonesian Stock Exchange in 2018. Data analysis using Moderated Regression Analysis (MRA). The results of this study indicate that family ownership does not affect tax aggressiveness, corporate governance has a positive effect on tax aggressiveness, and corporate governance strengthens the relationship between family ownership and tax aggressiveness. The research implication is that it can be an input in making decisions for the government regarding taxation, for companies related to decision making regarding corporate governance, as well as for investors for investment decisions.